Konseling Spiritual: Solusi Efektif untuk Mengatasi Body Dissatisfaction - Abdi, Sofyan; Nurfadillah, Fikri (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2025)
The research conducted aims to see whether there is a significant effectiveness between the provision of services in the form of spiritual counseling with body dissatisfaction behavior in students, as a form of effort to make students feel more satisfied with their body condition or shape. This type of research is experimental quantitative research with a single subject research design with the A-B-A phase conducted at MAN 2 Kota Bekasi. The population in this study is class XII with a sample that has been determined using purposive sampling technique as many as 2 students as research samples. Based on the Paired Sample T Test hypothesis test output, the Sig. (2-tailed) obtained is 0.002. if the Sig. (2-tailed) value obtained is less than 0.05 then there is a significant difference in body dissatisfaction behavior in students before and after getting spiritual counseling treatment or intervention. So it can be concluded that spiritual counseling is effective for reducing body dissatisfaction behavior in students at MAN 2 Kota Bekasi.